Stress and anxiety management intervention to enhance mental well-being among students of SMK Muhammadiyah Kartasura - Widodo, Arif; Oktaviana, Wita; Azani, Muhammad Zakki; Indahsari, Madya Maya; Nurtiningtyas, Vivi; Febriani, Diana; Agustin, Diva Penni (Community Empowerment, 2025)
The rising prevalence of mental health issues among adolescents, particularly stress and anxiety, necessitates effective interventions within the school environment. This community service program aims to identify and reduce anxiety and stress levels among 325 students at SMK Muhammadiyah Kartasura. The methodology involved initial surveys, in-depth interviews, and coping skills-based interventions. Results indicated that the "normal stress" category improved from 90% to 93.3%, while mild to moderate anxiety levels were significantly suppressed from 8.2% to 2.7%. These findings confirm that integrated stress management interventions in schools effectively improve adolescent psychological well-being. This program recommends incorporating stress management into the school curriculum and fostering collaborative support between parents and the community to cultivate a mentally healthy educational environment.